The man next door - Roberts, Sheila, 1951- (Mira Books, 2025)
Zona never thought her life was headed this way, but here she is, newly divorced and moving back in with her mom, Louise. After her gambling addicted ex-husband lost all of their savings, including their daughter's college fund, she doesn't really have a choice. She's cutting every coupon she can and she's going to help put her daughter through nursing school, even if it kills her. This wasn't Louise's plan, either, laid up at home with a broken leg after one unfortunate tumble on the senior singles cruise she'd been looking forward to for months. But if she's going to spend all her time at home, at least she's got her daughter there with her. And there's some hot new eye candy next door to distract them both from their troubles. He appears to be single and just around Zona's age. Could his arrival be the universe making amends for everything it's put her through? Maybe the universe isn't feeling as generous as Louise hoped. There's something lurking under that mans surface charm, something ... dangerous? And who's the woman they can hear him in all-out shouting matches with on the other side of the fence? When the woman seems to disappear without a trace, imaginations run wild. Or at least, Zona hopes it's just her mother's imagination ...